Mallocybe africana (Inocybaceae, Fungi), the first species of Mallocybe described from Africa - Aignon, Hyppolite L.; Naseer, Arooj; Matheny, Brandon P.; Yorou, Nourou S.; Ryberg, Martin (Phytotaxa, 2021)
The family Inocybaceae has been poorly studied in Africa. Here we describe the first species of the genus Mallocybe from West African and Zambian woodlands dominated by ectomycorrhizal trees of Fabaceae and Phyllanthaceae. The new species M. africana is characterized by orange-brown fruitbodies, a fibrillose pileus, a stipe tapered towards the base and large ellipsoid basidiospores. It resembles many north and south temperate species of Mallocybe but is most closely related to the southeast Asian tropical species, M. errata. M. africana is widely distributed in West Africa (Benin, Togo, Burkina Faso and Ivory Coast) extending to South-eastern Africa in Zambia. Phylogenetic analyses based on 5.8S rDNA, nLSU and RPB2 sequence data confirm that M. africana is nested within Mallocybe. A complete morphological description and illustrations, including photographs and line drawings, are presented.